Mediating Language, Culture, and Identity: Intersections of Applied Linguistics, Language Teaching, and Translation Studies - Amirsheibani, Morteza; Rustamov Uktam o'g'li, Dastonjon (International Journal of Educational Research & Social Sciences, 2026)
Translation and interpreting are often defined as the technical transfer of linguistic forms across languages, yet in contemporary contexts of globalization, mobility, and intercultural exchange they function as far more than mechanical processes. They operate as acts of mediation that bridge not only words but also cultures, identities, and emotions. This article situates translation and interpreting within a broader applied linguistics perspective, drawing connections with English language teaching (ELT), where educators face similar challenges of negotiating meaning, fostering intercultural awareness, and shaping learners’ identities. Both translators and teachers, rather than serving as neutral conduits, act as cultural mediators who must engage critically with the affective, social, and ideological dimensions of language. To illustrate this argument, the article draws on examples from research into nostalgia in migration discourses, humor in pedagogy, and the pragmatics of slang, which reveal how language embodies cultural memory, belonging, and emotional resonance that resist reduction to lexical equivalence. These cases highlight the limitations of narrow approaches centered on accuracy and equivalence while underscoring the value of reflexivity, empathy, and intercultural competence. The paper also explores the role of corpus-assisted discourse analysis as a methodological bridge that can enrich both translation and pedagogical practice by uncovering subtle discourse patterns and ideological cues. By integrating insights from applied linguistics, ELT, and translation studies, the article advocates for an interdisciplinary framework that reconceptualizes translation and interpreting as transformative acts of cultural mediation, contributing to more inclusive and dialogic forms of global communication.